2022
DOI: 10.1111/bju.15920
|View full text |Cite
|
Sign up to set email alerts
|

Surgical checklist adherence across urology expertise levels impacts transurethral resection of bladder tumour quality indicators

Abstract: To address the association of perioperative surgical checklist across variable surgical expertise with transurethral resection of bladder tumour (TURBT) accuracy and oncological outcomes in non-muscle-invasive bladder cancer. Patients and MethodsWe relied on our prospective collaborative database of patients treated with TURBT between 2012 and 2017. Surgical experience was stratified into three groups: resident vs young vs expert consultants. The association of surgical experience with detrusor muscle (DM) pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The omission of records of risk factors related to recurrence and progression is expected to be reduced while the quality of resection will be improved by checking these items during surgery. All reports on statistically evaluated risk factor record rates found significant improvements after the implementation of the surgical checklist 10,21,25 . In addition, all checklists, except the two surgical checklists that did not include the presence or absence of muscle layer 22 and were introduced after a muscle collection rate of over 90%, 23 were associated with an increase in the rate of muscle collection, and the two reports showed a statistically significant improvement 10,25 .…”
Section: Impact Of Surgical Checklists On Quality and Outcomes Of Turbtsmentioning
confidence: 97%
See 3 more Smart Citations
“…The omission of records of risk factors related to recurrence and progression is expected to be reduced while the quality of resection will be improved by checking these items during surgery. All reports on statistically evaluated risk factor record rates found significant improvements after the implementation of the surgical checklist 10,21,25 . In addition, all checklists, except the two surgical checklists that did not include the presence or absence of muscle layer 22 and were introduced after a muscle collection rate of over 90%, 23 were associated with an increase in the rate of muscle collection, and the two reports showed a statistically significant improvement 10,25 .…”
Section: Impact Of Surgical Checklists On Quality and Outcomes Of Turbtsmentioning
confidence: 97%
“…Surgical experience and volume are associated with complications, recurrence, and survival risk 20 . However, a study reported that the experience of the surgeon was not associated with the presence of the DM in resected specimens and the 5‐year recurrence‐free survival (RFS) after TURBTs in the case of adequate perioperative surgical checklist implementation 25 . On the other hand, excessive attention by a surgical checklist to the presence of the DM in the resection specimen and excessively deep excision may increase the risk of bladder perforation.…”
Section: Impact Of Surgical Checklists On Quality and Outcomes Of Turbtsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of detrusor muscle in the specimen is a recognized surrogate parameter for the quality of the resection [3]. The reported rate of detrusor muscle obtained with conventional TURBT (TURBT) ranges from 54 to 95% [4 ▪ ,5 ▪▪ ], and is also dependent on surgical experience [6,7]. TURBT is based on tumour fragmentation and separate resection of the exophytic part of the tumour, the underlying bladder wall and the edges of the resection area [1].…”
Section: Introductionmentioning
confidence: 99%